2019
DOI: 10.17557/tjfc.631130
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Adaptability of Sorghum Hybrids Elucidated With Genotype–environment Interaction Biplots

Abstract: This study was conducted to compare the performance of ten sorghum hybrids at two locations (Maize and Millets Research Institute, Yusafwala, Sahiwal, MMRI) & Sorghum Research Sub-Station, Dera Gazi Khan, D.G. Khan) for two consecutive years (2015 and 2016), i.e. in a total of four environments (MMRI-15, MMRI-16, DG Khan-15 and DG Khan-16). The experiment was conducted in a Randomized Complete Block Design with a plot size of 4 × 0.75 × 2 m. In all four environments the crop was sown in July and harvested in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Comparison biplot model have been used to determine the optimal genetypes for adaptation studies. Similar results using the GGE Biplot model have been reported by several other researchers (Dehghani et al, 2006;Kaya et al, 2006;Akcura et al, 2011;Jalata, 2011;Rakhsit et al, 2012;Karimizade et al, 2013;Kendal and Sayar, 2016;Oral et al, 2018;Muntaz 2019).The stability of the genotypes in dry matter yield was assessed using the biplot (Figure 17). The ASV indicated variations in dry matter yield stability among five maize hybrids (Table 6).…”
Section: The Gge Biplot Analysis Of Dry Matter Yieldsupporting
confidence: 79%
See 2 more Smart Citations
“…Comparison biplot model have been used to determine the optimal genetypes for adaptation studies. Similar results using the GGE Biplot model have been reported by several other researchers (Dehghani et al, 2006;Kaya et al, 2006;Akcura et al, 2011;Jalata, 2011;Rakhsit et al, 2012;Karimizade et al, 2013;Kendal and Sayar, 2016;Oral et al, 2018;Muntaz 2019).The stability of the genotypes in dry matter yield was assessed using the biplot (Figure 17). The ASV indicated variations in dry matter yield stability among five maize hybrids (Table 6).…”
Section: The Gge Biplot Analysis Of Dry Matter Yieldsupporting
confidence: 79%
“…The study conducted in the same environment for six years showed that the years were different from each other in terms of herbage yield of maize genotypes ( Figure 6). The effect of this method on the environment is different from each other (Yan and Tinker 2006;Putto et al, 2008;Ahmadi et al, 2012;Muntaz et al, 2019).…”
Section: The Gge Biplot Analysis For Herbage Yieldmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore, these two clusters could be used in hybridization programs to broaden the genetic basis of germplasm, and top entries from cluster-2 could be directly resealed for general cultivation if their performance in multilocation trials remains as good as in this experiment. Several researchers used cluster and biplot analysis to characterize genotypes under the different environmental conditions and found these tools quite useful [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to classical methods, different stability analyzes such as multivariate analysis (Westcoff, 1987), cluster analysis (Crossa et al, 1991), regression analysis (Gauch, 1988), additive main effects and multiplicative interaction model (Gauch, 1992) are used to explain the genotype x environment interaction. The most powerful and optimal technique recently used is the genotype x environment biplot technique owing to providing a visual presentation of the interactions (Yan et al, 2001;Dehghani et al, 2006;Mumtaz et al, 2019). Tobacco selection in the natural population do not allow to obtain a new genotype, only an existing individual is highlighted.…”
Section: Introductionmentioning
confidence: 99%